Irresponsibility and Identity in Meredith's Modern Love - Blume, Rebecca Lillian (My University, 1981)
Critics have generally thought that George Meredith's discussion of marital breakdown in Modern Love was in advance of its time. It must be granted that the married couple in the poem do not conform to the image that the Victorians liked to project of themselves, but in my view the narrator's attitude toward his wife, in fact, reflects a very conventional Victorian standpoint. Instead of taking an honest look at the marriage, the narrator blames his wife and unseen forces for their problems. The narrator's share of responsibility is revealed, however, in his manner of narration, in his responses to his wife, and in his way of handling his problems when he begins to suspect her adultery.
When the narrator places the blame beyond himself, he has the least awareness of and control over his life. When he accepts responsibility for some of the blame for the failed marriage, he is generally stronger, and able to influence the course of his life, instead of yielding to invisible forces. Because of his weak sense of self the narrator is paralyzed by conflict and is unable to take effective action to improve his situation.
Keywords: English; English Language and Literature; English Language and Literature